BIOFAQs - BIOFiltration and AQuaculture: An evaluation of substrate deployment performance with mariculture developments - Black K.D.; Sayer M.D.J.; Cook E.; Angel D.; Spanier E.; Karakassis I.; Malej A.; Colins K.; Pickering H.; Whitmarsh D.; Lojen S. (Environmental impact assessment of Mediterranean aquaculture farms, 2001)
A significant proportion of mariculture is undertaken in Europe under intensive farming conditions in open cage culture. Wastes are dispersed from cage farms as particulate organic carbon and nutrients, dissolved organic carbon and inorganic nutrients. These enrich the surrounding ecosystem and may stimulate both primary and secondary production. This pan-European research project will demonstrate the effectiveness of reducing the environmental impacts of inputs from intensive cage mariculture by using biological filters ('biofilters'). They are designed to offer complex surfaces for colonisation by both sessile and mobile biota, which will absorb the effluents from the fish farms and potentially increase the sustainability of coastal aquaculture. Validated model predictions will be used to assist in optimising biofilter design and placement in line with geographical differences across Europe. Environmental and regulatory options governing post-biofilter usage will also be examined and economic analyses of biofilter use compared with existing practices will be provided.
TECAM Seminar on Environmental Impact Assessment of Mediterranean Aquaculture Farms, 2000/01/17-21, Zaragoza (Spain)